Ultrabroadband near-infrared emission profiling in multicore optical fibers doped with Er3+ and Yb3+/Tm3+/Ho3+ ions - Jakub Markiewicz; Marcin Kochanowicz; Tomasz Ragiń; Piotr Miluski; Wojciech A. Pisarski; Joanna Pisarska; Marta Kuwik; Dominik Dorosz; Martin Leich; Matthias Jäger (Scientific Reports)
Abstract This paper presents novel multicore fibers with broadband emission in the 1.4–2.1 μm range. Based on our previous work with barium gallo-germanate glasses and fibers, the 4 and 11-core fiber structures, each containing core glasses doped with Er3+ and Yb3+/Tm3+/Ho3+, were developed. Our efforts have resulted in flat emission in 3 dB and 10 dB bands, achievable under excitation at 796 nm, 808 nm, 940 nm, and 980 nm. The measured emission spectra of these fibers are described as a superposition of emission bands from each individual core, corresponding to the transitions of Er3+, Tm3+, and Ho3+ ions. Our method demonstrates the potential of emission profiling in multicore optical fibers as a new way to construct eye-safe broadband fiber sources.